Middle turbinate concha bullosa and its relationship with chronic sinusitis: a review - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Sinonasal diseases are serious health issues found in the clinical practice. Sinonasal diseases are often associated with anatomical variants in the sinonasal tract. There are numerous sinonasal anatomical variants found frequently in computed tomography (CT) scans of the paranasal sinuses. Middle turbinate concha bullosa is a common anatomical variant found in the nasal cavity. Pneumatization of the middle turbinate is called as concha bullosa. The pneumatization of the middle turbinate is mostly via the anterior ethmoidal air cells. Pneumatizations through posterior ethmoid air cells are also reported. There are three types of concha bullosa such as lamellar, bulbous and extensive. Majority of the patients with middle turbinate concha bullosa are asymptomatic. Sometimes this is accidentally detected during proper evaluation of the headache. Sometimes the middle turbinate concha bullosa is associated with chronic sinusitis. However, there are very few literatures which correlate the middle turbinate concha bullosa and chronic sinusitis. Although chronic sinusitis is a clinical diagnosis, the imagings like CT scan are useful to assess the extent of the disease and demonstrate the sinonasal anatomy. CT scan of the paranasal sinuses and diagnostic nasal endoscopy are important tests useful for evaluation of the middle turbinate concha bullosa and its relations with chronic sinusitis. This review article discusses on the details of the middle turbinate concha bullosa and its relationship with chronic sinusitis.